Frequency of Nonobstructive Coronary Artery Disease in patients admitted for Elective Coronary Angiography - Adnan Fazal, Fawad Ali Siddiqui, Muhammad Haroon Afzal, Usama Masood, Kashif Shahzad, Abdul Rahman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cardiovascular disease specially ischemic heart disease in Pakistan has become one of the major cause of mortality. Patients with symptoms/signs of angina non obstructive CAD may be suspected where atherosclerotic epicardial CAD does not limit coronary blood flow, but other processes may disturb myocardial supply/demand relationship Objective: To determine the frequency of nonobstructive coronary artery disease in patients admitted for elective coronary angiography, at NICVD, Karachi, Pakistan Methods: This Cross sectional study was done at National Institute of Cardiovascular Disease (NICVD), Karachi, Pakistan from April 16, 2021 to October 15, 2021. we included patients fulfilling the inclusion criteria. Informed consent was taken. The data was collected on prepared proforma. Results: Mean ± SD of age was 55.4±13.2 years. Out of 151 patients, 90 (59.6%) were male while 61 (40.4%) were female, Hypertension was noted in 105 (69.5%) patients while Diabetes mellitus was documented in 71 (47%) patients and Positive family history of nonobstructive CAD was found to be in 26 (17.2%) patients , and 67 (44.4%) were smoker. Nonobstructive CAD was found to be in 35 (23.2%) patients. Conclusion: It is to be concluded that nonobstructive coronary artery disease was documented in considerable number of patients admitted for elective coronary angiography. Further large-scale work is recommended for validation of current findings.